Preparation method of copper-doped bi-crosslinked asphalt-based porous carbon and product and application of copper-doped bi-crosslinked asphalt-based porous carbon
By using copper-doped double crosslinked asphalt-based porous carbon as the substrate for silicon carbon anode material in lithium-ion batteries, the problem of electrochemical performance degradation caused by volume changes in silicon materials is solved, and the cost of porous carbon preparation is reduced, achieving high conductivity, excellent mechanical properties, and good cycle stability and rate performance.
Patent Information
- Application Number
- CN202411785555.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-06
AI Technical Summary
In existing lithium-ion batteries, silicon, as the negative electrode material, has caused the material to powder and fall off due to volume expansion and contraction during the lithium-embedded deliquency process, and loses electrochemical performance. At the same time, the cost of porous carbon preparation process is high, which limits the development of industrialization.
Copper-doped double-crosslinked asphalt-based porous carbon is used as the substrate for silicon carbon anode material. By adding cuproamin solution and asphalt to the cellulose solution, the porous carbon with high conductivity and excellent mechanical properties is formed by preoxidation and crosslinking, pre-carbonization and activation treatment.
The high conductivity and mechanical properties of copper-doped double-crosslinked asphalt-based porous carbon are achieved, the cycle stability and rate performance of silicon carbon anode materials are enhanced, and the production cost is reduced.
Smart Images

Figure CN119637845A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a preparation method of copper-doped double-crosslinked asphalt-based porous carbon, and its products and applications. Background Art
[0002] Silicon is currently the negative electrode material with the largest theoretical capacity, with a specific capacity of up to 4200mAh / g, which is much higher than the theoretical capacity of graphite (the theoretical capacity of graphite-based negative electrode materials is only 372mAh / g). Silicon has the advantages of low lithium insertion potential and low cost, and is expected to replace graphite as the next generation of lithium-ion battery negative electrode material. However, as a negative electrode material, silicon is accompanied by severe volume expansion and contraction during the lithium insertion and de-lithiation process, which makes the material easy to pulverize, fall off the current collector, and lose electrochemical performance.
[0003] Due to the structural stability of carbon materials, the volume change during the charge and discharge process is relatively small, and it has good cycle stability. In addition, it has similar chemical properties to silicon, so silicon and carbon are often compounded to improve the volume expansion effect of silicon and improve its electrochemical stability. Porous carbon has been widely used in the preparation of new vapor-deposited silicon-carbon composite materials, but the high cost of porous carbon preparation technology has limited the industrial development of new silicon-carbon negative electrodes. The development of highly economical porous carbon products has strong appeal to existing scientific research fields and enterprises.
[0004] Asphalt has a high carbon mass ratio and is an ideal precursor for preparing porous carbon. However, asphalt contains a large number of conjugated benzene ring structures, which easily form a graphite-like structure, resulting in a low strength of the porous carbon skeleton and limited tolerance to the expansion of the silicon negative electrode. In addition, asphalt-based porous carbon has limited improvement in conductivity.
[0005] In response to the above problems, most researchers have introduced pre-oxidation processes and modifiers to improve the carbon skeleton strength and conductivity of asphalt-based porous carbon. For example, a Chinese patent document with application publication number CN118206115A discloses a high-performance asphalt-based porous carbon material and a method for preparing the same, the method comprising: step one, mixing coal tar and carbon nanotubes to obtain a precursor; step two, pre-treating and crushing the precursor; step three, adding graphene and drying; step four, pre-oxidation treatment; step five, carbonization and activation treatment. This technical solution constructs a multi-dimensional additive network by introducing a variety of carbon materials, such as graphene and carbon nanotubes, for filling and modification, which effectively improves the carbon skeleton strength and conductivity of asphalt-based porous carbon. The conductivity of the finished porous carbon reaches 25S cm at 130MPa. -1The particle strength reaches above 3.0GPa. However, the preparation price of graphene and carbon nanotubes is relatively high, and large-scale production is not easy. In addition, the preparation process involves multiple uneven physical mixing processes, which may lead to poor consistency in the local conductivity and skeleton strength distribution of porous carbon, which is not conducive to the production of the final silicon-carbon negative electrode. Summary of the invention
[0006] In response to the above problems, the present invention discloses a method for preparing copper-doped double-cross-linked asphalt-based porous carbon. The prepared asphalt-based porous carbon has high conductivity and excellent mechanical properties. The silicon-carbon negative electrode material prepared with it as the substrate has excellent cycle stability and rate performance.
[0007] To achieve the above purpose, the specific technical solution of the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing copper-doped double-crosslinked asphalt-based porous carbon, comprising:
[0009] S1: dissolving cellulose in a copper ammonia solution to obtain a uniform solution, then adding asphalt, mixing thoroughly, and then heating and drying to obtain a copper ammonia cellulose@asphalt composite material;
[0010] S2: heating the copper amino cellulose@asphalt composite material for pre-oxidation cross-linking, and then pre-carbonizing it under a protective atmosphere to obtain a carbonized material;
[0011] S3: activating the carbonized material to obtain copper-doped double-crosslinked asphalt-based porous carbon.
[0012] The present invention firstly uses a copper ammonia solution to completely dissolve the insoluble cellulose to obtain a uniform solution. This process not only provides a prerequisite for the subsequent sufficient cross-linking between cellulose molecules and asphalt molecules, but also introduces copper elements into the porous carbon to reduce its powder resistance. The subsequent pre-oxidation cross-linking forms a double cross-linking structure (cross-linking between asphalt molecules and additional cross-linking between cellulose molecules and asphalt molecules through bridging oxygen), which jointly improves the overall hardness of the material. The hard carbon nanowires with a cellulose molecular skeleton are distributed throughout the three-dimensional asphalt matrix space, limiting the excessive expansion of nano silicon particles inside the porous carbon. Finally, asphalt-based porous carbon is prepared after pre-carbonization and activation treatment. During the pre-carbonization and activation treatment, the introduced copper element will reduce the high-valent copper to elemental copper and / or low-valent copper, thereby reducing the powder resistance of the porous carbon substrate and thereby increasing the conductivity of the silicon-carbon negative electrode. It is found that the introduction of copper and the introduction of cellulose produce synergy, further improving the particle strength of the asphalt-based porous carbon, and being more conducive to slowing down the volume expansion of silicon particles.
[0013] In an optional embodiment, step S1 includes at least one of the following features (1) to (7):
[0014] (1) The cellulose includes but is not limited to one or more of α-cellulose, β-cellulose, microcrystalline cellulose, and carboxymethyl cellulose, with a number average molecular weight of 2000 to 15000;
[0015] Optionally, the cellulose is selected from one or more of α-cellulose, β-cellulose, and microcrystalline cellulose; further optionally, the cellulose is selected from α-cellulose.
[0016] Optionally, the number average molecular weight of the cellulose is 5000-15000.
[0017] (2) The copper ammonia solution is prepared by a method comprising: chemically reacting a 10-20 wt% copper salt solution with a 5-15 wt% alkali solution to generate a copper hydroxide precipitate, separating and washing the precipitate, and then dripping 15-25 wt% ammonia water until the precipitate dissolves;
[0018] Optionally, the copper salt solution is selected from soluble aqueous solutions of copper, specifically selected from conventional types in the art, such as copper nitrate, copper sulfate, copper chloride, and the like.
[0019] Optionally, the alkali solution is selected from aqueous alkali solutions, specifically selected from conventional types in the art; optionally, the alkali is selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like.
[0020] (3) preparing the homogeneous solution at a low temperature of -15 to -5°C;
[0021] (4) The mass ratio of cellulose to copper ammonia solution is 1:(4-16);
[0022] Optionally, the mass ratio of cellulose to the copper ammonia solution is 1:(4-8); further optionally, the mass ratio of cellulose to the copper ammonia solution is 1:8.
[0023] (5) The asphalt is in powder form with a particle size of D 50 3~9μm, D max ≤50μm;
[0024] Optionally, the asphalt is selected from conventional types in the art, such as petroleum asphalt, coal asphalt, mesophase asphalt, naphthalene asphalt, etc.; further optionally, the asphalt is selected from petroleum asphalt or coal asphalt.
[0025] (6) The mass ratio of cellulose to asphalt is 1:(25-100);
[0026] Optionally, the mass ratio of cellulose to asphalt is 1:(25-50); further optionally, the mass ratio of cellulose to asphalt is 1:50.
[0027] (7) The heating and drying process has a temperature of 60 to 90°C.
[0028] The purpose of the drying is to remove the solvent in the system to obtain a fully mixed composite solid.
[0029] In an optional embodiment, in step S2:
[0030] Optionally, the pre-oxidation cross-linking is performed at a temperature of 250-350°C.
[0031] Optionally, the pre-oxidation cross-linking time is 1 to 5 hours.
[0032] Optionally, the pre-oxidation cross-linking has a heating rate of 0.5 to 5°C / min.
[0033] Optionally, the pre-oxidation cross-linking is carried out in a rotary kiln, the air flow rate is controlled to be 0.5 to 10 L / min, and the rotation speed of the rotary kiln is controlled to be 5 to 10 rpm.
[0034] Optionally, the pre-carbonization treatment is carried out under a protective atmosphere, and the protective atmosphere includes one or more of nitrogen, argon and helium.
[0035] Optionally, the pre-carbonization treatment is performed at a temperature of 600-800°C.
[0036] Optionally, the pre-carbonization treatment is carried out for 4 to 10 hours.
[0037] Optionally, the pre-carbonization treatment has a heating rate of 0.5 to 20° C. / min.
[0038] In an optional embodiment, in step S3, the activation treatment comprises at least one of the following features (1) to (4):
[0039] (1) The activation treatment is selected from physical activation, and the activating agent is selected from CO, CO 2 , water vapor, oxygen or one or more thereof;
[0040] Optionally, the activator is selected from CO, CO 2 , water vapor or one or more of the following.
[0041] (2) The activation treatment is carried out at a temperature of 700 to 1000°C; optionally, the temperature is 800 to 900°C.
[0042] (3) The activation treatment time is 2 to 15 hours;
[0043] (4) In the activation treatment, the flow rate of the activating agent is 0.01 to 5 kg / h.
[0044] Optionally, in the activation treatment, the flow rate of the activating agent is 0.1 to 2.5 kg / h.
[0045] Optionally, the activation treatment has a heating rate of 0.5 to 20° C. / min.
[0046] Optionally, the activation treatment is carried out in a rotary kiln, and the rotation speed of the rotary kiln is controlled to be 0.5-10 rpm.
[0047] In the second aspect, the present invention also provides copper-doped double-crosslinked asphalt-based porous carbon prepared according to the above method, which has a particle strength of not less than 4.1 GPa and a powder resistance of not more than 0.17 Ω·cm at 20 MPa; it has both high strength and high conductivity.
[0048] In a third aspect, the present invention also provides a method for preparing a silicon-carbon negative electrode material, which is prepared by using the copper-doped double-cross-linked asphalt-based porous carbon as a substrate and sequentially performing silicon deposition and carbon coating.
[0049] In an optional embodiment, the silicon deposition comprises at least one of the following features (1) to (7):
[0050] (1) The raw material gas used in the silicon deposition includes a silicon source gas;
[0051] Optionally, the silicon source gas is selected from conventional types in the art, including one or more of monosilane, disilane, dichlorosilane, and trichlorosilane.
[0052] (2) The flow rate of the raw gas is 1 to 50 L / h;
[0053] (3) The silicon is deposited at a temperature of 300 to 800° C.;
[0054] (4) The silicon deposition time is 1 to 40 hours;
[0055] (5) The raw material gas also includes a carrier gas;
[0056] (6) The carrier gas is selected from nitrogen and / or argon;
[0057] (7) Based on the total volume of the raw gas being 100%, the volume proportion of the carrier gas is 1 to 30%.
[0058] In an optional embodiment, the carbon coating comprises at least one of the following features (1) to (6):
[0059] (1) The raw material gas used in the carbon coating includes a carbon-containing gas;
[0060] (2) The carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; optionally, the C1-C4 alkanes are selected from methane, ethane, propane, and butane; optionally, the C2-C4 alkenes are selected from ethylene, propylene, butene, and 1,3-butadiene; optionally, the C2-C4 alkynes are selected from acetylene, propyne, and butyne.
[0061] (3) The flow rate of the carbon-coated raw gas is 1 to 10 L / h;
[0062] (4) The carbon coating is performed at a temperature of 400 to 1200° C.;
[0063] (5) The carbon coating time is 1 to 10 hours;
[0064] (6) The carbon-coated raw gas also includes an inert gas.
[0065] Optionally, the inert gas is selected from conventional types in the art, such as nitrogen, argon, etc.
[0066] In a fourth aspect, the present invention also provides a silicon-carbon negative electrode material prepared according to the above method.
[0067] In a fifth aspect, the present invention further provides a lithium-ion battery comprising the above-mentioned silicon-carbon negative electrode material.
[0068] Compared with the prior art, the present invention has the following beneficial results:
[0069] The present invention discloses a method for preparing asphalt-based porous carbon. Initial pre-oxidation causes cross-linking between asphalt molecules, and cellulose molecules and asphalt produce additional cross-linking through bridging oxygen. The double cross-linking structure jointly improves the overall hardness of the material. Hard carbon nanowires with cellulose molecular skeletons are distributed throughout the three-dimensional asphalt matrix space, limiting the excessive expansion of nano silicon particles inside the porous carbon. Furthermore, copper has good ductility and conductivity. The copper element remaining in the raw material liquid is incorporated into the asphalt matrix in the pre-carbonization step. In the subsequent activation process, the high-valent copper is reduced to elemental copper and / or low-valent copper, which not only cooperates with the production of the introduced cellulose to further improve the particle strength of the asphalt-based porous carbon, but is also more conducive to slowing down the volume expansion of silicon particles. It also reduces the powder resistance of the porous carbon substrate, thereby increasing the conductivity of the silicon-carbon negative electrode. In addition, since the substances contained in the prepared precursor are all required for the subsequent reaction, acid washing is not required, which simplifies the production steps and reduces the processing cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 The present invention is a flow chart of the method for preparing copper-doped double-crosslinked asphalt-based porous carbon;
[0071] Figure 2This is a structural diagram of α-cellulose used in Example 1 of the present invention;
[0072] Figure 3 The scanning electron microscope mapping selection range (a) and the distribution of copper elements in the selection range (b) of the pitch-based porous carbon in Example 1 of the present invention. DETAILED DESCRIPTION
[0073] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0074] In the description of the present invention, it should be noted that, for those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood in specific circumstances. Below, according to the overall structure of the present invention, its embodiments are described. Unless otherwise specified, the raw materials in the embodiments of the present invention are purchased through commercial channels.
[0075] In a first aspect, the present invention provides a method for preparing copper-doped double-crosslinked asphalt-based porous carbon, comprising:
[0076] S1: dissolving cellulose in a copper ammonia solution to obtain a uniform solution, then adding asphalt, mixing thoroughly, and then heating and drying to obtain a copper ammonia cellulose@asphalt composite material;
[0077] S2: heating the copper amino cellulose@asphalt composite material for pre-oxidation cross-linking, and then pre-carbonizing it under a protective atmosphere to obtain a carbonized material;
[0078] S3: activating the carbonized material to obtain copper-doped double-crosslinked asphalt-based porous carbon.
[0079] The present invention firstly uses a copper ammonia solution to completely dissolve the insoluble cellulose to obtain a uniform solution. This process not only provides a prerequisite for the subsequent sufficient cross-linking between cellulose molecules and asphalt molecules, but also introduces copper elements into the porous carbon to reduce its powder resistance. The subsequent pre-oxidation cross-linking forms a double cross-linking structure (cross-linking between asphalt molecules and additional cross-linking between cellulose molecules and asphalt molecules through bridging oxygen), which jointly improves the overall hardness of the material. The hard carbon nanowires with a cellulose molecular skeleton are distributed throughout the three-dimensional asphalt matrix space, limiting the excessive expansion of nano silicon particles inside the porous carbon. Finally, asphalt-based porous carbon is prepared after pre-carbonization and activation treatment. During the pre-carbonization and activation treatment, the introduced copper element will reduce the high-valent copper to elemental copper and / or low-valent copper, thereby reducing the powder resistance of the porous carbon substrate and thereby increasing the conductivity of the silicon-carbon negative electrode. It is found that the introduction of copper and the introduction of cellulose produce synergy, further improving the particle strength of the asphalt-based porous carbon, and being more conducive to slowing down the volume expansion of silicon particles.
[0080] In an optional embodiment, step S1 includes at least one of the following features (1) to (7):
[0081] (1) The cellulose includes but is not limited to one or more of α-cellulose, β-cellulose, microcrystalline cellulose, and carboxymethyl cellulose, with a number average molecular weight of 2000 to 15000;
[0082] Optionally, the cellulose is selected from α-cellulose, β-cellulose, and microcrystalline cellulose.
[0083] The experiment found that compared with α-cellulose, β-cellulose and microcrystalline cellulose, the solution viscosity of carboxymethyl cellulose is higher, the uniformity of liquid phase mixing is lower, and the particle strength of the prepared asphalt-based porous carbon is slightly reduced.
[0084] Further optionally, the cellulose is selected from α-cellulose.
[0085] The number average molecular weight of the cellulose may be 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000, 12000, 13000, 14000, 15000 or any value within the above range. Optionally, the number average molecular weight of the cellulose is 5000-15000.
[0086] It was found through experiments that the particle strength of the prepared pitch-based porous carbon is related to the number average molecular weight of the cellulose used.
[0087] (2) The copper ammonia solution is prepared by a method comprising: chemically reacting a 10-20 wt% copper salt solution with a 5-15 wt% alkali solution to generate a copper hydroxide precipitate, separating and washing the precipitate, and then dripping 15-25 wt% ammonia water until the precipitate dissolves;
[0088] Optionally, the copper salt solution is selected from a soluble aqueous solution of copper, specifically selected from conventional types in the art, such as copper nitrate, copper sulfate, copper chloride, etc. The concentration of the copper salt solution can specifically be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt% or any value within the above range.
[0089] Optionally, the alkali solution is selected from aqueous alkali solutions, specifically selected from conventional types in the art; optionally, the alkali is selected from lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. The concentration of the alkali solution can specifically be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt% or any value within the above range.
[0090] Optionally, the concentration of the ammonia water can be specifically 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt% or any value within the above range.
[0091] (3) The uniform solution is prepared at a low temperature of -15 to -5°C; specifically, it can be -15°C, -14°C, -13°C, -12°C, -11°C, -10°C, -9°C, -8°C, -7°C, -6°C, -5°C or any value within the above range.
[0092] (4) The mass ratio of cellulose to copper ammonia solution is 1:(4-16); specifically, it can be 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16 or any ratio within the above range. Optionally, the mass ratio of cellulose to copper ammonia solution is 1:(4-8); further optionally, the mass ratio of cellulose to copper ammonia solution is 1:8.
[0093] Experiments have shown that with the optimization of the mass ratio of the cellulose to the copper ammonia solution, the particle strength and conductivity of the prepared asphalt-based porous carbon are better.
[0094] (5) The asphalt is in powder form with a particle size of D 503 to 9 μm, specifically 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm or any value within the above range; D max ≤50μm, specifically can be 0.1μm, 0.5μm, 1μm, 2μm, 4μm, 3μm, 4μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm or any value within the above range.
[0095] Optionally, the asphalt is selected from conventional types in the art, such as petroleum asphalt, coal asphalt, mesophase asphalt, naphthalene asphalt, etc.; further optionally, the asphalt is selected from petroleum asphalt or coal asphalt.
[0096] (6) The mass ratio of cellulose to asphalt is 1:(25-100); specifically, it can be 1:25, 1:50, 1:55, 1:60, 1:65, 1:70, 1:75, 1:80, 1:85, 1:90, 1:95, 1:100, 1:16 or any ratio within the above range.
[0097] Optionally, the mass ratio of cellulose to asphalt is 1:(25-50); further optionally, the mass ratio of cellulose to asphalt is 1:50.
[0098] Experiments have shown that with the optimization of the mass ratio of cellulose to asphalt, the particle strength and conductivity of the prepared asphalt-based porous carbon are even better.
[0099] (7) The heating and drying temperature is 60-90°C, specifically 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value within the above range.
[0100] The purpose of the drying is to remove the solvent in the system to obtain a fully mixed composite solid.
[0101] In an optional embodiment, in step S2:
[0102] Optionally, the pre-oxidation cross-linking temperature is 250-350°C, specifically 250°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C or any value within the above range.
[0103] Optionally, the pre-oxidation cross-linking time is 1 to 5 hours, specifically 1 hour, 1.5 hours, 2.0 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours or any value within the above range.
[0104] Optionally, the pre-oxidation cross-linking has a heating rate of 0.5 to 5°C / min, specifically 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min or any value within the above range.
[0105] Optionally, the pre-oxidation cross-linking is carried out in a rotary kiln, and the air flow rate is controlled to be 0.5-10 L / min, specifically 0.5 L / min, 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min or any value within the above range; the rotation speed of the rotary kiln is controlled to be 5-10 rpm, specifically 5 rpm, 6 rpm, 7 rpm, 8 rpm, 9 rpm, 10 rpm or any value within the above range.
[0106] Optionally, the pre-carbonization treatment is carried out under a protective atmosphere, and the protective atmosphere includes one or more of nitrogen, argon and helium.
[0107] Optionally, the pre-carbonization treatment is carried out at a temperature of 600-800°C, specifically 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C or any value within the above range.
[0108] Optionally, the pre-carbonization treatment time is 4 to 10 h, specifically 4.0 h, 4.5 h, 5.0 h, 5.5 h, 6.0 h, 6.5 h, 7.0 h, 7.5 h, 8.0 h, 8.5 h, 9.0 h, 9.5 h, 10 h or any value within the above range.
[0109] Optionally, the pre-carbonization treatment has a heating rate of 0.5 to 20°C / min, specifically 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 15°C / min, 20°C / min or any value within the above range.
[0110] In an optional embodiment, in step S3, the activation treatment comprises at least one of the following features (1) to (4):
[0111] (1) The activation treatment is selected from physical activation, and the activating agent is selected from CO, CO 2 , water vapor, oxygen or one or more thereof;
[0112] Optionally, the activator is selected from CO, CO 2 , water vapor or one or more of the following.
[0113] (2) The activation treatment is carried out at a temperature of 700-1000°C, specifically 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 950°C, 1000°C or any value within the above range; optionally, the temperature is 800-900°C.
[0114] (3) The activation treatment time is 2 to 15 hours, specifically 2 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or any value within the above range.
[0115] (4) In the activation treatment, the flow rate of the activator is 0.01 to 5 kg / h, specifically 0.01 kg / h, 0.05 kg / h, 0.1 kg / h, 0.5 kg / h, 1 kg / h, 1.5 kg / h, 2 kg / h, 2.5 kg / h, 3 kg / h, 3.5 kg / h, 4 kg / h, 4.5 kg / h, 5 kg / h or any value within the above range; optionally, in the activation treatment, the flow rate of the activator is 0.1 to 2.5 kg / h.
[0116] Optionally, the activation treatment has a heating rate of 0.5 to 20°C / min, specifically 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, 20°C / min or any value within the above range.
[0117] Optionally, the activation treatment is carried out in a rotary kiln, and the rotation speed of the rotary kiln is controlled to be 0.5-10rpm, specifically 0.5rpm, 1rpm, 2rpm, 3rpm, 4rpm, 5rpm, 6rpm, 7rpm, 8rpm, 9rpm, 10rpm or any value within the above range.
[0118] In the second aspect, the present invention also provides copper-doped double-crosslinked asphalt-based porous carbon prepared according to the above method, which has a particle strength of not less than 4.1 GPa and a powder resistance of not more than 0.17 Ω·cm at 20 MPa; it has both high strength and high conductivity.
[0119] In a third aspect, the present invention also provides a method for preparing a silicon-carbon negative electrode material, which is prepared by using the copper-doped double-cross-linked asphalt-based porous carbon as a substrate and sequentially performing silicon deposition and carbon coating.
[0120] In an optional embodiment, the silicon deposition comprises at least one of the following features (1) to (7):
[0121] (1) The raw material gas used in the silicon deposition includes a silicon source gas;
[0122] Optionally, the silicon source gas is selected from conventional types in the art, including one or more of monosilane, disilane, dichlorosilane, and trichlorosilane.
[0123] (2) The flow rate of the raw gas is 1 to 50 L / h, specifically 1 L / h, 2 L / h, 3 L / h, 5 L / h, 10 L / h, 15 L / h, 20 L / h, 25 L / h, 30 L / h, 35 L / h, 40 L / h, 45 L / h, 50 L / h or any value within the above range.
[0124] (3) The silicon deposition temperature is 300-800°C, specifically 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or any value within the above range.
[0125] (4) The silicon deposition time is 1 to 40 hours, specifically 1 hour, 5 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours or any value within the above range.
[0126] (5) The raw material gas also includes a carrier gas;
[0127] (6) The carrier gas is selected from nitrogen and / or argon;
[0128] (7) Taking the total volume of the raw gas as 100%, the volume proportion of the carrier gas is 1 to 30%, specifically 1%, 5%, 8%, 10%, 15%, 18%, 20%, 25%, 28%, 30% or any value within the above range.
[0129] In an optional embodiment, the carbon coating comprises at least one of the following features (1) to (6):
[0130] (1) The raw material gas used in the carbon coating includes a carbon-containing gas;
[0131] (2) The carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; optionally, the C1-C4 alkanes are selected from methane, ethane, propane, and butane; optionally, the C2-C4 alkenes are selected from ethylene, propylene, butene, and 1,3-butadiene; optionally, the C2-C4 alkynes are selected from acetylene, propyne, and butyne.
[0132] (3) The flow rate of the carbon-coated raw gas is 1 to 10 L / h, specifically 1 L / h, 2 L / h, 3 L / h, 4 L / h, 5 L / h, 6 L / h, 7 L / h, 8 L / h, 9 L / h, 10 L / h or any value within the above range.
[0133] (4) The carbon coating has a temperature of 400-1200°C, specifically 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C or any value within the above range.
[0134] (5) The carbon coating time is 1 to 10 hours, specifically 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3.0 hours, 3.5 hours, 4.0 hours, 4.5 hours, 5.0 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours or any value within the above range.
[0135] (6) The carbon-coated raw gas also includes an inert gas.
[0136] Optionally, the inert gas is selected from conventional types in the art, such as nitrogen, argon, etc.
[0137] In a fourth aspect, the present invention also provides a silicon-carbon negative electrode material prepared according to the above method.
[0138] In a fifth aspect, the present invention further provides a lithium-ion battery comprising the above-mentioned silicon-carbon negative electrode material.
[0139] Example 1
[0140] S1. A 15wt% copper nitrate aqueous solution and a 10wt% sodium hydroxide aqueous solution react to form a copper hydroxide precipitate. The precipitate is separated and washed, and 20wt% ammonia water is added dropwise until the precipitate is dissolved to prepare a copper ammonia solution. At -10°C, α-cellulose (number average molecular weight of 12000) and copper ammonia solution are dissolved in a mass ratio of (1kg:8kg) to obtain a uniform solution. Under strong stirring, a particle size D 50 5μm, Dmax 50 kg of 30 μm powdered petroleum asphalt was added to the above uniform solution, and the mixture was stirred and mixed for 10 hours, and then dried at 80° C. to obtain a copper amino cellulose@asphalt composite material;
[0141] S2. Place 50 kg of the composite material in a tubular furnace, introduce air at a flow rate of 5 L / min, heat it to 300°C at 5°C / min and keep it warm for 4 hours to pre-oxidize the asphalt, then switch to nitrogen. When the oxygen content drops below 30 ppm, heat it to 700°C at 5°C / min to pre-carbonize the composite material for 6 hours.
[0142] S3, placing 30 kg of the pre-carbonized material in a rotary furnace, setting the rotation rate to 5 r / min, heating to 850°C at 10°C / min for steam activation to obtain asphalt-based porous carbon, the steam flow rate is 0.5 kg / h, and the activation time is 12 h;
[0143] The doping distribution of copper on the surface of the material was observed using a scanning electron microscope. Figure 3 This is a mapping diagram of the copper element on the surface of the asphalt-based porous carbon prepared in step S3 of this embodiment. It is observed that the copper element is evenly distributed on the porous carbon.
[0144] Example 2
[0145] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of the added α-cellulose is replaced with 2 kg.
[0146] Example 3
[0147] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of the added α-cellulose is replaced with 0.5 kg.
[0148] Example 4
[0149] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of the added copper ammonia solution is replaced with 4 kg.
[0150] Example 5
[0151] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of the added copper ammonia solution is replaced with 16 kg.
[0152] Example 6
[0153] The preparation process is substantially the same as that of Example 1, except that in step S1, α-cellulose is replaced with an equal mass of β-cellulose (number average molecular weight of 5000).
[0154] Example 7
[0155] The preparation process is substantially the same as that of Example 1, except that in step S1, α-cellulose is replaced with an equal mass of microcrystalline cellulose (number average molecular weight of 3000).
[0156] Example 8
[0157] The preparation process is substantially the same as that of Example 1, except that in step S1, α-cellulose is replaced with an equal mass of carboxymethyl cellulose (number average molecular weight of 2200).
[0158] Comparative Example 1
[0159] The preparation process is basically the same as that of Example 1, except that in step S1, α-cellulose is not added, that is, 50 kg of powdered petroleum asphalt is directly added to 8 kg of copper ammonia solution, stirred and mixed for 10 hours, and then dried at 80° C. to obtain the composite material.
[0160] Comparative Example 2
[0161] The preparation process is basically the same as that of Example 1, except that in step S1, the copper ammonia solution is replaced with deionized water of equal mass, that is, 50 kg of powdered petroleum asphalt is directly added to 8 kg of deionized water, stirred and mixed for 10 hours, and then dried at 80° C. to obtain the composite material.
[0162] Comparative Example 3
[0163] The preparation process is basically the same as that of Example 1, except that in step S1, the α-cellulose is replaced with an epoxy resin (Shanghai Guangyan Chemical Technology Co., Ltd., brand: 618, model: ZZZF04031) of equal mass as a reinforcing agent.
[0164] Comparative Example 4
[0165] The preparation process is substantially the same as that of Example 1, except that in step S1, the mass of the added copper ammonia solution is replaced with 32 kg.
[0166] Comparative Example 5
[0167] S1. Disperse 1 kg of α-cellulose in 8 kg of 10 wt% sodium hydroxide aqueous solution and mix the particles to obtain a cellulose slurry of D 50 5μm, D max 50 kg of 30 μm powdered petroleum asphalt was added to the above solution, and then 1.5 kg of copper nitrate powder was added. The mixture was stirred and mixed for 10 hours and then dried at 80° C. to obtain a copper nitrate-modified cellulose@asphalt composite material.
[0168] Steps S2 to S3 are exactly the same as those in Example 1.
[0169] The performance data of the asphalt-based porous carbon prepared in each embodiment and comparative example are listed in the following Table 1, wherein the element content is obtained by ICP-MS testing, the specific surface area and pore distribution are obtained by a precise high-precision nitrogen adsorption and desorption test system, and the powder resistance is obtained by a ST2722B four-terminal powder resistivity tester. In the process of strength testing the particles, particles of similar particle size are selected and measured by the strength tester.
[0170] Table 1
[0171]
[0172]
[0173] Comparing Examples 1 to 3 in Table 1, the porous carbon prepared in Example 1 has better comprehensive physical indicators and excellent comprehensive electrochemical performance; while the porous carbon powder prepared in Example 2 has slightly increased resistance and slightly decreased particle strength, which may be due to the increased amount of cellulose, increased oxygen content, and overlapping behavior of cellulose chains; the particle strength of the porous carbon prepared in Example 3 decreases, which may be due to the decreased amount of cellulose.
[0174] By comparing Examples 1, 4 to 5 and Comparative Example 4, the resistance of the porous carbon prepared in Example 4 increases and the particle strength decreases slightly, which may be due to the decrease in the amount of copper ammonia solution used and the reduction in the copper content; the particle strength of the porous carbon prepared in Example 5 also decreases, which may be due to the increase in the amount of copper ammonia solution used. During carbonization, the interface between the asphalt and the cellulose carbon is separated by copper, and the strength is slightly reduced; and the particle strength of the porous carbon prepared in Comparative Example 4 decreases significantly, which is caused by a large excess of copper ammonia solution.
[0175] Compared with Examples 1, 6 to 8, the particle strength of the porous carbon prepared in Examples 6 and 7 is slightly lower than that in Example 1, which may be because the number average molecular weight of cellulose used in Examples 6 and 7 is lower than that in Example 1; the particle strength of the porous carbon prepared in Example 8 is the lowest, which may be due to the high viscosity of the carboxymethyl cellulose solution and the low liquid phase mixing uniformity, resulting in a decrease in the strength of the asphalt-based porous carbon particles.
[0176] Comparing Example 1 with Comparative Example 1 and Comparative Example 3, in Comparative Example 1, no cellulose was added, and the particle strength of the prepared porous carbon was extremely low; in Comparative Example 3, other common reinforcing agent epoxy resin was used instead of cellulose, and the reinforcing effect was not ideal.
[0177] Comparing Example 1 with Comparative Example 2 and Comparative Example 5, no copper ammonia solution was added in Comparative Example 2, that is, no copper element was introduced, which not only greatly improved the powder resistance of the porous carbon, but also unexpectedly found that the particle strength was significantly lower than that of Example 1, which shows that the addition of copper element can also produce synergy with cellulose to further improve the particle strength of the porous carbon. In Comparative Example 5, the particle strength of the prepared porous carbon was significantly reduced and the powder resistance was significantly increased by first dissolving cellulose with alkali solution and then adding copper salt, which may be caused by uneven dispersion of cellulose.
[0178] Application Examples
[0179] 10 kg of the asphalt-based porous carbon prepared in each embodiment and comparative example was placed in a rotary kiln as a substrate, and a raw gas composed of monosilane gas and nitrogen was introduced at 500°C, the raw gas flow rate was 9 L / h, and the deposition time was 25 hours. The carbon coating process was to put the above silicon-carbon material into a rotary kiln, introduce acetylene gas, and carry out the process under nitrogen protection and high temperature of 700°C, the acetylene gas flow rate was 4 L / h, and the carbon coating time was 8 hours.
[0180] The products prepared in each embodiment and each comparative example are used as negative electrode materials to assemble batteries.
[0181] (1) Preparation of positive electrode sheets: The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the conductive agent SuperP, carbon nanotubes, the binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70 wt%), which was coated on both sides of the current collector aluminum foil, dried at 100°C, and cold pressed at 4 MPa at room temperature, and then trimmed, cut, and slit, and the tabs were welded to form positive electrode sheets.
[0182] (2) Preparation of negative electrode sheets: Under a nitrogen protective atmosphere, the solvent N-methylpyrrolidone (NMP) and the binder PVDF were stirred and mixed, and then the conductive agent SuperP was added and stirred and mixed. Then, the final product prepared in each embodiment and each comparative example was added as the negative electrode active material and stirred and mixed thoroughly to prepare a negative electrode slurry (solid content of 50wt%).
[0183] The negative electrode slurry is coated on both sides of the current collector copper foil, dried at 100°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, stripped, and the tabs are welded to make negative electrode sheets.
[0184] (3) Assembly of lithium-ion batteries
[0185] Using PE porous polymer film as separator, the prepared positive electrode sheet, separator and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic shell package and placed under a relative vacuum pressure of -0.95×10 5 Pa, dried at 100 ° C to less than 100 ppm of moisture. The electrolyte is injected into the dried bare battery, wherein the electrolyte consists of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M), and packaged, static, formed (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaped, and capacity tested (divided capacity) to make a soft-pack liquid lithium-ion battery. When assembling the battery, five batteries are prepared for each test, and a total of five groups of data are tested. The final performance takes the average of the five groups of data.
[0186] The battery cycle performance was tested on a blue-electric device, specifically: at 25°C, first discharge to 0.005V at 0.1C, then discharge to 0.001V at 0.08C, discharge to 0.001V at 0.05C, discharge to 0.001V at 0.02C, and let stand for 10 minutes; then charge to 1.5V at 0.1C, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 100 times in the above manner, record the charge and discharge capacity after 100 times, and calculate the capacity retention rate after 100 cycles. The expansion test is obtained by disassembling the battery after the battery cycle and comparing the thickness of the electrode before and after the cycle; the rate performance test is to increase the charge and discharge rate to 2C on the basis of the cycle test. The specific test / calculation results are shown in Table 2 below.
[0187] Table 2
[0188]
[0189]
[0190] Comparing Examples 1 to 8 in Table 2, the silicon-carbon negative electrode materials prepared in each example have excellent cycle stability and high rate performance, but the electrochemical performance of the product prepared in Example 1 is the best. Due to the slight difference in powder resistance and particle strength of the porous carbon substrate itself, the cycle retention rate, expansion rate and rate performance of the silicon-carbon negative electrode materials prepared in other examples are slightly different.
[0191] Comparing Example 1 with Comparative Examples 1, 3 and 5, the silicon-carbon negative electrode materials prepared in Comparative Examples 1, 3 and 5 respectively have poor cycle stability and large expansion rate, which is related to the low particle strength of the porous carbon substrate itself used.
[0192] Comparative Example 1 and Comparative Examples 2 and 4, the rate performance of the silicon-carbon negative electrode materials prepared in Comparative Examples 2 and 4 respectively decreased significantly, which is related to the high powder resistance of the porous carbon substrate itself used therein.
[0193] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A method for preparing copper-doped double-crosslinked asphalt-based porous carbon, characterized in that: include: S1: dissolving cellulose in a copper ammonia solution to obtain a uniform solution, then adding asphalt, mixing thoroughly, and then heating and drying to obtain a copper ammonia cellulose@asphalt composite material; S2: heating the copper amino cellulose@asphalt composite material for pre-oxidation cross-linking, and then pre-carbonizing it under a protective atmosphere to obtain a carbonized material; S3: activating the carbonized material to obtain copper-doped double-crosslinked asphalt-based porous carbon.
2. The method for preparing copper-doped double-crosslinked pitch-based porous carbon according to claim 1, characterized in that: Step S1 includes at least one of the following features (1) to (7): (1) The cellulose includes but is not limited to one or more of α-cellulose, β-cellulose, microcrystalline cellulose, and carboxymethyl cellulose, with a number average molecular weight of 2000 to 15000; (2) The copper ammonia solution is prepared by a method comprising: chemically reacting a 10-20 wt% copper salt solution with a 5-15 wt% alkali solution to generate a copper hydroxide precipitate, separating and washing the precipitate, and then dripping 15-25 wt% ammonia water until the precipitate dissolves; (3) preparing the homogeneous solution at a low temperature of -15 to -5°C; (4) The mass ratio of cellulose to copper ammonia solution is 1:(4-16); (5) The asphalt is in powder form with a particle size of D 50 3~9μm, D max ≤50μm; (6) The mass ratio of cellulose to asphalt is 1:(25-100); (7) The heating and drying process has a temperature of 60 to 90°C.
3. The method for preparing copper-doped double-crosslinked pitch-based porous carbon according to claim 1, characterized in that: In step S2: The pre-oxidation cross-linking is carried out at a temperature of 250 to 350° C. and a time of 1 to 5 hours; The pre-carbonization treatment uses a protective atmosphere including one or more of nitrogen, argon and helium, a temperature of 600 to 800° C., and a time of 4 to 10 hours.
4. The method for preparing copper-doped double-crosslinked pitch-based porous carbon according to claim 1, characterized in that: In step S3, the activation treatment includes at least one of the following features (1) to (4): (1) The activation treatment is selected from physical activation, and the activating agent is selected from one or more of CO, CO2, water vapor, and oxygen; (2) The activation treatment is performed at a temperature of 700 to 1000° C. (3) The activation treatment lasts for 2 to 15 hours; (4) In the activation treatment, the flow rate of the activating agent is 0.01 to 5 kg / h.
5. A copper-doped double-crosslinked pitch-based porous carbon prepared according to the method according to any one of claims 1 to 4, characterized in that: The particle strength is not less than 4.1 GPa, and the powder resistance under 20 MPa is not higher than 0.17 Ω·cm.
6. A method for preparing a silicon-carbon negative electrode material, characterized in that: The copper-doped double-crosslinked asphalt-based porous carbon as claimed in claim 6 is used as a substrate, and silicon deposition and carbon coating are performed in sequence to prepare the carbon substrate.
7. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The silicon deposition comprises at least one of the following features (1) to (7): (1) The raw material gas used in the silicon deposition includes a silicon source gas; (2) The flow rate of the raw gas is 1 to 50 L / h; (3) The silicon is deposited at a temperature of 300 to 800° C.; (4) The silicon deposition time is 1 to 40 hours; (5) The raw material gas also includes a carrier gas; (6) The carrier gas is selected from nitrogen and / or argon; (7) Based on the total volume of the raw gas being 100%, the volume proportion of the carrier gas is 1 to 30%.
8. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The carbon coating comprises at least one of the following features (1) to (6): (1) The raw material gas used in the carbon coating includes a carbon-containing gas; (2) the carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; (3) The flow rate of the carbon-coated raw gas is 1 to 10 L / h; (4) The carbon coating is performed at a temperature of 400 to 1200° C.; (5) The carbon coating time is 1 to 10 hours; (6) The carbon-coated raw gas also includes an inert gas.
9. A silicon-carbon negative electrode material prepared according to the method according to any one of claims 6 to 8.
10. A lithium ion battery, characterized in that: Comprising the silicon-carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Hierarchical porous carbon material used for flexible supercapacitor and production method thereof
CN109850866A
Silicon-based negative electrode material and preparation method thereof
CN116914112A
High-performance asphalt-based porous carbon material and preparation method thereof
CN118206115A
Silicon carbon negative electrode material, and preparation method therefor and use thereof
WO2024221285A1